1969
DOI: 10.1084/jem.130.5.1063
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Studies on Streptococci

Abstract: Extensive chemical and immunological studies have characterized the group A streptococcal cell wall as composed of four major components: M protein (and related T and R antigens), carbohydrate, mucopeptide, and glycerol teichoic acid (1, 2). These cell wall constituents, along with an external capsule and an underlying cytoplasmic membrane, are important in determining the relationship between group A streptococci and their human hosts (3). Our aim is to define the morphology and location of each of the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
128
0
2

Year Published

1973
1973
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(143 citation statements)
references
References 18 publications
13
128
0
2
Order By: Relevance
“…Outside the wall only short thick projections were seen, with no layer external to them. These projections in no way resembled the surface fimbriae which have been demonstrated in group A streptococci (Swanson et al, 1969). When ruthenium red was not used for staining, no structures were visible external to the wall.…”
Section: R E S U L T Smentioning
confidence: 88%
“…Outside the wall only short thick projections were seen, with no layer external to them. These projections in no way resembled the surface fimbriae which have been demonstrated in group A streptococci (Swanson et al, 1969). When ruthenium red was not used for staining, no structures were visible external to the wall.…”
Section: R E S U L T Smentioning
confidence: 88%
“…To determine whether the NTSAI antigen(s) represented a deeper structure of the cell wall or, perhaps, an extension of the underlying protoplast +Type 24 streptococci that lost their resistance to phagocytosis after multiple subculttires in laboratory media. membrane through the cell wall, fresh human serum, which contained NTSM antibody, was absorbed with 2 mg /ml of cell walls, purified cell wall mucopeptide, or protoplast membranes (Table VIII).…”
Section: Resultsmentioning
confidence: 99%
“…These fimbriae-like structures (3,24) appear to carry the unique TSM antigenic determinant that is exposed on the surface of fully "virulent" organisms. The deeper NTSM-associated part of the fimbriae may arise at the protoplast membrane and may be continuous with, but lie proximal to, the TSM.…”
Section: Discussionmentioning
confidence: 99%
“…Fimbriae could possibly represent slender extensions of the membrane that penetrate the cell wall. This particular cellular location of the membrane antigens might explain why past attempts to clearly separate wall and membrane antigens have not been fruitful (166,256). Dale and Beachey (51) recently showed that a purified preparation of group A streptococcal type 5 M-protein contained an antigen within it which elicited heart reactive antibody, implying that it was the component responsible for cross-reactivity.…”
Section: Possible Role Of Immunological Mechanisms In the Diseasementioning
confidence: 99%
“…Both antigens were shown to absorb heart antibodies from human sera (16). The possibility was therefore considered that the same antigen(s) was present on protoplast membranes as well as on the fimbriae-like structures that protrude through the cell wall and that contain Mprotein (256). It has been speculated that membrane antigens (fimbriae) are present at the outer surface of the cell, a location that might contribute to their antigenicity.…”
Section: Possible Role Of Immunological Mechanisms In the Diseasementioning
confidence: 99%